The Development of an Instructional Model Based on Constructivist Theory and Phenomenon-Based Learning to Enhance Curriculum Development and Learning Management Abilities of Pre-Service Teachers - Witchayawat, Wilaiphorn (Dhammathas Academic Journal, 2026)
This study aimed to 1) develop and validate an instructional model based on constructivist theory and Phenomenon-based Learning, and 2) examine the effectiveness of the developed model. A quasi-experimental research design was employed. The sample, obtained through cluster random sampling, consisted of 60 second-year pre-service teachers at the University of Phayao in the 2023 academic year. They were divided into an experimental group of 30 students who learned through the developed model and a control group of 30 students who received lecture-based instruction with guided practice. The research instruments included the instructional model, an achievement test, and rubric-based assessments of curriculum development and instructional design competencies. Data were analyzed using mean, standard deviation, t-test, and analysis of covariance (ANCOVA). The findings were as follows: 1. The developed instructional model was rated at the highest level of appropriateness and feasibility. The model comprised five components: principles, objectives, a learning process, assessment, and a support system, with a six-step learning process: 1) observing and selecting a phenomenon, 2) understanding the phenomenon, 3) investigating for answers, 4) creating products, 5) presenting and evaluating products, and 6) applying knowledge. 2. Regarding the model’s effectiveness, pre-service teachers in both groups showed significantly higher post-test achievement scores than pre-test scores at the .01 level of significance. When comparing post-test achievement scores between the two groups using analysis of covariance, a statistically significant difference was found at the .05 level, with the experimental group outperforming the control group. Furthermore, the experimental group demonstrated significantly higher competencies in curriculum development and instructional design than the control group at the .05 level of significance.